2015
DOI: 10.1117/12.2199217
|View full text |Cite
|
Sign up to set email alerts
|

Microscale resolution fracture toughness profiling at the zirconia-porcelain interface in dental prostheses

Abstract: The high failure rate of the Yttria Partially Stabilized Zirconia (YPSZ)-porcelain interface in dental prostheses is influenced by the micro-scale mechanical property variation in this region. To improve the understanding of this behavior, micro-scale fracture toughness profiling by nanoindentation micropillar splitting is reported for the first time. Sixty 5 μm diameter micropillars were machined within the first 100 μm of the interface. Berkovich nanoindentation provided estimates of the bulk fracture toughn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…These results include those presented in Figure 4, as well as those obtained from the re-evaluation of ring-core FIB milling data previously reported by Lunt et al [31,32]. Micro-scale mechanical testing of the YPSZ-porcelain interface has recently been performed to determine the spatial variation of fracture toughness through micropillar splitting [15], as well as the Young's modulus and yield strength from micropillar compression [14] ( Figure 6b). The results of recent energy dispersive spectroscopy studies have also been included to provide insight into the elemental variation in the near-interface region (Figure 6c) [14].…”
Section: Compendium Of Mechanical Microscopy Of the Ypsz-porcelain Insupporting
confidence: 74%
See 2 more Smart Citations
“…These results include those presented in Figure 4, as well as those obtained from the re-evaluation of ring-core FIB milling data previously reported by Lunt et al [31,32]. Micro-scale mechanical testing of the YPSZ-porcelain interface has recently been performed to determine the spatial variation of fracture toughness through micropillar splitting [15], as well as the Young's modulus and yield strength from micropillar compression [14] ( Figure 6b). The results of recent energy dispersive spectroscopy studies have also been included to provide insight into the elemental variation in the near-interface region (Figure 6c) [14].…”
Section: Compendium Of Mechanical Microscopy Of the Ypsz-porcelain Insupporting
confidence: 74%
“…The results of this study can therefore be used as a firm basis to optimise models of YPSZ-porcelain prosthesis manufacture, and ultimately aid in reducing failure rates in future. [14,15]. c) Spatial variation of seven highest weight % elements obtained using energy dispersive spectroscopy [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies into the origin of this behaviour have suggested that failure arises from modifications to the microstructure (and mechanical behaviour) of porcelain within the first few microns of the interface [4][5][6][7] . Although elemental diffusion is known to influence this weakened near interface region, the primary driving force behind many of these mechanical changes is the tensile residual stress (or strain) which is generated during manufacture [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This technique is based on indentation with a sharp indenter on pillars produced using focused ion beam (FIB) machining with an aspect ratio (height-to-diameter) greater than 1. This allows local interrogation of materials toughness with high resolution [9,10]. In sufficiently brittle materials, a crack nucleates underneath the indenter during loading, and at some critical instability, the crack extends out to the pillar surface.…”
Section: Introductionmentioning
confidence: 99%